2014
DOI: 10.1002/2014gl061475
|View full text |Cite
|
Sign up to set email alerts
|

Pore‐scale intermittent velocity structure underpinning anomalous transport through 3‐D porous media

Abstract: 19.12.14 KB. Ok to add published version to spiral after 6 months embargo - expires 15 March 201

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

12
200
0

Year Published

2015
2015
2017
2017

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 153 publications
(232 citation statements)
references
References 43 publications
(54 reference statements)
12
200
0
Order By: Relevance
“…The resulting flow fields provide valuable data to study the microscopic transport process in detail. Furthermore, this data gives important guidance for the development of effective models that can be applied to simulate flow and transport at scales larger than the pore scale [19,20]. For example, Kang et al [19] studied the advection-dominated dispersion in Berea sandstone based on a flow field stemming from micro-CT scanning and pore-scale DNS.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The resulting flow fields provide valuable data to study the microscopic transport process in detail. Furthermore, this data gives important guidance for the development of effective models that can be applied to simulate flow and transport at scales larger than the pore scale [19,20]. For example, Kang et al [19] studied the advection-dominated dispersion in Berea sandstone based on a flow field stemming from micro-CT scanning and pore-scale DNS.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, this data gives important guidance for the development of effective models that can be applied to simulate flow and transport at scales larger than the pore scale [19,20]. For example, Kang et al [19] studied the advection-dominated dispersion in Berea sandstone based on a flow field stemming from micro-CT scanning and pore-scale DNS. They found that the dispersion in longitudinal direction is superdiffusive, with the variance of tracer particle positions scaling with time to the power of 1.5.…”
Section: Introductionmentioning
confidence: 99%
“…In the three dimensions, it was found [3] that the transverse velocity autocorrelation decays faster, though the absolute value is strongly correlated in time, a feature also observed in turbulent flows [5]. These remarkable properties have led to the suggestion that the Lagrangian particle velocities is given by a Markov process in space (at equidistant positions along the Lagrangian trajectories) and not in time [6,7].…”
Section: Introductionmentioning
confidence: 97%
“…In a Markov process the particle motion can be seen as a correlated continuous time random walk (CTRW). Using a correlated CTRW, several signatures of anomalous transport behavior were accurately reproduced such as the long tails of the first passage time distribution [6], the non-linear scaling of the second centered moment of the particles longitudinal and transverse displacements [3,6,8], the probability distribution function of the Lagrangian velocity increments for different time lags among others [1].…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation